무균성 뇌수막염 소아에서 뇌척수액내 Matrix Metalloproteinase(MMP)-9과 Tissue Inhibitor of Metalloproteinase(TIMP)-1의 증가 - 양주희; 박민혁; 심정연; 정혜림; 박문수; 금동혁; Yang, Ju Hee; Park, Min Hyuk; Shim, Jung-Yeon; Jung, Hye Lim; Park, Moon Soo; Keum, Dong Hyuck (Soakwa, 2003)
Purpose : Matrix metalloproteinase(MMP)-9 is known to breakdown the blood-brain barrier by degrading the extracellular matrix of the subendothelial basement membrane in meningitis. Tissue inhibitor of metalloproteinase(TIMP)-1, a known inhibitor of MMP-9, has been postulated to inhibit the proteolytic activity of MMP-9 by bindng to MMP-9, but their interaction has not been fully understood yet. So far, there have been some reports on the relationship of MMP-9 and TIMP-1 in bacterial meningitis, but few reports in viral meningitis. Furthermore, there has been no report on this in Korea. We investigated the concentrations of MMP-9 and TIMP-1 in cerebrospinal fluid (CSF) and serum of patients with viral meningitis and control subjects, and evaluated their relationship with other clinical parameters of meningitis. Methods : CSF and blood were obtained from 25 subjects with viral meningitis and 14 control subjects. After centrifugation, supernatants were stored at $-20^{°}C$ and we assayed concentrations of MMP-9 and TIMP-1 by the sandwich ELISA method. Results : Concentrations of CSF MMP-9 and TIMP-1 were significantly elevated in patients with viral meningitis, when compared with those in control subjects. Their serum levels showed no differences between the two groups. MMP-9 levels were closely correlated with TIMP-1 levels in the CSF($r_s=0.42$, P<0.05). CSF MMP-9/TIMP-1 ratios were significantly higher in patients with viral meningitis than those in the control subjects(P<0.05). Both CSF MMP-9 and TIMP-1 levels positively correlated with CSF total leukocyte counts($r_s=0.43$, P<0.05, $r_s=0.48$, P<0.05). TIMP-1 levels positively correlated with total protein concentrations in the CSF($r_s=0.43$, P<0.05). Conclusion : MMP-9 and TIMP-1 may play an important role in the breakdown and maintenance of BBB in viral meningitis, respectively. 목 적 : 뇌수막염에서 MMP-9은 뇌혈관 내피하 기질막을 분해하여 혈관-뇌장벽을 파괴하는데 주된 역할을 담당하며 TIMP-1은 MMP-9의 전효소와 복합체를 형성하여 MMP-9의 작용을 선택적으로 억제하는 인자로 알려져 있으나 이들의 상호작용은 아직 밝혀진 바가 별로 없다. 최근 세균성 뇌수막염 환자의 뇌척수액에서 MMP-9과 TIMP-1 측정에 대한 연구가 있었고, 특히 세균성 뇌수막염에서 신경학적 합병증의 예후인자와 관련하여 MMP-9의 역할에 대한 보고들이 있었으나 아직 무균성 뇌수막염 환자를 대상으로 한 보고는 별로 없었고 특히 국내에서 보고된 바는 없었다. 이에 저자들은 무균성 뇌수막염 환아의 혈액과 뇌척수액에서 MMP-9과 TIMP-1의 농도를 측정하여 대조군과 비교하고, MMP-9과 TIMP-1 및 다른 뇌수막염 관련인자들 사이의 상관관계를 비교 분석하고자 하였다. 방 법: 2002년 6월부터 7월까지 강북삼성병원 소아과 내원환자 중 발열과 뇌막자극증상을 보인 40명의 환아들을 대상으로 뇌척수액 검사를 시행하여, 무균성 뇌수막염 소견을 보인 25명을 뇌수막염군, 정상소견을 보인 14명을 대조군으로 하였다. 입원당일 혈액과 뇌척수액을 채취하여 혈액에서 백혈구수를 측정하고, 뇌척수액에서 백혈구수와, 당, 단백농도 및 뇌압을 측정하였다. 나머지 혈액 및 뇌척수액 검체는 실온에서 10분간 2,000g으로 원심분리하여 영하 70도에서 보관후 sandwich ELISA 방법을 이용하여 각각의 검체에서 일시에 MMP-9과 TIMP-1의 농도를 정량하였다. 결 과 : 뇌척수액 MMP-9과 TIMP-1 농도는 뇌수막염군에서 의미있게 증가되었고(P<0.05), 혈청 MMP-9과 TIMP-1 농도는 두 군간에 차이가 없었다. 뇌척수액 MMP-9과 TIMP-1은 서로 의미있는 양의 상관관계를 보였으며($r_s=0.42$, P<0.05), 뇌척수액 MMP-9/TIMP-1 비율은 대조군에 비해 무균성 뇌수막염군에서 의미있게 증가되었다(P<0.05). 뇌척수액 MMP-9과 TIMP-1은 뇌척수액 총백혈구수와 양의 상관관계를 보였다($r_s=0.43$, P<0.05, $r_s=0.48$, P<0.05). 뇌척수액 TIMP-1은 뇌척수액 단백 농도와 양의 상관관계를 보였다($r_s=0.43$, P<0.05). 결 론 : 무균성 뇌수막염 환아의 급성기 뇌척수액에서 MMP-9과 TIMP-1이 의미있는 증가를 보였고, 뇌척수액 TIMP-1은 정상군에서 상대적으로 높은 농도를 보이고 있어 MMP-9과 TIMP-1은 각각 뇌혈관장벽의 파괴와 유지에 관여한다고 생각된다.